2021
DOI: 10.3389/fendo.2021.635995
|View full text |Cite
|
Sign up to set email alerts
|

Ceramides and Sphingosino-1-Phosphate in Obesity

Abstract: Obesity is a growing worldwide problem, especially in developed countries. This disease adversely affects the quality of life and notably contributes to the development of type 2 diabetes, metabolic syndrome, and cardiovascular disorders. It is characterised by excessive lipids accumulation in the subcutaneous and visceral adipose tissue. Considering the secretory function of adipose tissue, this leads to impaired adipokines and cytokines release. Changes in adipose tissue metabolism result in chronic inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
(79 reference statements)
0
7
0
Order By: Relevance
“… 61 , 62 And 2-amino-8-oxo-9,10-epoxy-decanoic acid is a sphingolipid-like compound that is structurally related to sphingosine, and alterations in sphingolipid metabolism can potentially lead to insulin resistance, inflammation, and adipose tissue dysfunction, all of which are associated with obesity. 63 , 64 As childhood obesity is a considerable risk factor for precocious puberty, 5 this study proposes that the prevention of obesity-induced precocious puberty by reducing LH levels is mediated by the interplay between microbiota and metabolites within Factor 2. Additionally, seafood is a nutritious source of high-quality protein and essential nutrients such as vitamin D, vitamin B12, niacin, pantothenic acid, and omega-3 fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“… 61 , 62 And 2-amino-8-oxo-9,10-epoxy-decanoic acid is a sphingolipid-like compound that is structurally related to sphingosine, and alterations in sphingolipid metabolism can potentially lead to insulin resistance, inflammation, and adipose tissue dysfunction, all of which are associated with obesity. 63 , 64 As childhood obesity is a considerable risk factor for precocious puberty, 5 this study proposes that the prevention of obesity-induced precocious puberty by reducing LH levels is mediated by the interplay between microbiota and metabolites within Factor 2. Additionally, seafood is a nutritious source of high-quality protein and essential nutrients such as vitamin D, vitamin B12, niacin, pantothenic acid, and omega-3 fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tissue inflammation can induce insulin resistance [89,90]. Early investigations of ceramide-induced insulin resistance were performed primarily in skeletal muscle, and more recently, studies have confirmed that ceramides have been explored as an important mediators of insulin resistance in adipose and liver [20,[91][92][93] (Figure 4). Nevertheless, there are some contradictory findings on the role of ceramides in the induction of insulin resistance.…”
Section: Ceramides Induced Hepatic Insulin Resistancementioning
confidence: 99%
“…The majority of plasma S1P binds to apolipoprotein M (apoM), which mostly combines with HDL, and the remaining associates with albumin, LDLs, or VLDLs [ 94 ]. Interestingly, S1P contents increased in the subcutaneous WAT of obese diabetic patients, suggesting a connection between S1P and lipid metabolism [ 95 ]. When LDL receptor-deficient mice were fed with high CHO–Western diet and were treated with SKI-II (a sphingosine kinase 1 inhibitor that substantially reduces plasma S1P levels) for 16 weeks, their aortic atherosclerotic lesions increased, circulation TG levels decreased, without changing their body weight and plasma total/HDL CHO [ 96 ].…”
Section: Gut Microbiota Derived Evs Participate In Inflammation Modul...mentioning
confidence: 99%